Infectious Disease Risk Across the Growing Human-Non Human Primate Interface: A Review of the Evidence - Devaux, Christian A.; Mediannikov, Oleg; Medkour, Hacene; Raoult, Didier (Frontiers in Public Health, 2019)
Most of the human pandemics reported to date can be classified as zoonoses. Among these, there is a long history of infectious diseases that have spread from non-human primates (NHP) to humans. For millennia, indigenous groups that depend on wildlife for their survival were exposed to the risk of NHP pathogens' transmission through animal hunting and wild meat consumption. Usually, exposure is of no consequence or is limited to mild infections. In rare situations, it can be more severe or even become a real public health concern. Since the emergence of acquired immune deficiency syndrome (AIDS), nobody can ignore that an emerging infectious diseases (EID) might spread from NHP into the human population. In large parts of the Central Africa and Asia, wildlife still remains the primary source of meat and income for millions of people living in rural areas. However, in the past decades the risk of exposure to an NHP pathogen has taken a new dimension. Unprecedented breaking down of natural barriers between NHP and humans has increased exposure to health risks for a much larger population including people living in urban areas. There are several reasons to this: (i) due to road development and massive destruction of ecosystems for agricultural needs, wildlife and humans come more frequently into contact; (ii) due to the ecological awareness, many long distance travelers are in search of wildlife discovery, with a particular fascination for African great apes; (iii) due to attraction for ancient temples and mystical practices, others travelers visit Asian places colonized by NHP. In each case, there is a risk of pathogen transmission through bite or another route of infection. Beside the individual risk to contracting a pathogen, there is also a possibility of starting a new pandemic. This article reviews the known cases of NHP pathogens' transmission to humans whether they are hunters, travelers, ecotourists, veterinarians or scientists working on NHP. Although pathogen transmission is supposed to be a rare outcome, some pathogens including Rabies virus, Herpes B virus, Monkeypox virus, Ebola virus, or Yellow fever virus are of greater concern and require quick countermeasures from healthcare professionals.